Cultural Diversity in the Classroom A European Comparison - Spinthourakis, Julia Athena; Lalor, John.; Berg, Wolfgang; SpringerLink (Online service) (Wiesbaden : VS Verlag für Sozialwissenschaften, 2012)
The so-called nation states have created ethnical minorities. Also due to migration, cultural diversity is the reality. The multicultural society is strongly reproduced in the schools all over Europe. Cultural diversity in the classroom is increasingly recognized as a potential which should not be neglected. The educational system has, above all, to provide all children with equal opportunities. Experts from Finland, the UK, Hungary, Spain, Greece, Cyprus, and other European states, mostly responsible for teacher education, have contributed to this volume with critical, but constructive remarks on the classroom reality in their countries. This book is valuable reading for academics and practitioners in educational sciences.
Keywords: Social sciences; Social Sciences; Social Structure, Social Inequality; Sociology, general; Education (general).